EFFECT OF VITAMIN D3 AND K2 AS ADJUNCT TO PERIODONTAL THERAPY - MOHAMMED, NAREEN RAFEEQ; MOUSA, HASHIM DAWOOD (Journal of Duhok University, 2023)
Background and Objectives: chronic periodontitis is a prevalent disease among the adult population that can cause serious damage to the periodontal tissue. Vitamin D3 deficiency/insufficiency is a global public health issue that has been linked to various inflammatory disorders, including periodontitis. Vitamin K2 has recently gained importance as a potential therapeutic agent because it regulates body calcium metabolism. The use of Vitamin D3 and K2 supplementation as adjunctive during non-surgical periodontal treatment (NSPT) can help improve the treatment outcome and the severity of chronic periodontitis. Further research is needed to determine the optimal dosage and duration of supplementation required for maximum benefit.Material and methods: involved 45 systemically healthy patients between the ages of range 20-45 years viewing moderate to severe chronic periodontitis were selected and randomly divided into 3 groups, the control group (n= 15) received conventional periodontal treatment, Drug and SRP group (n=15) received conventional periodontal treatment with pharmaceutical intervention (Vit D3 5000 iu + K2 100mg ) for the treatment of vitamin D deficiency and Drug group (n=15) received the pharmaceutical intervention (Vit D3 5000 iu +K2 100mg) for the treatment of vitamin D deficiency. Result: Significant reductions in PI, GI, and CAL were detected after 2 months of non-surgical periodontal treatment (NSPT) with Vitamin D3 and K2 supplementation compared to baseline in both groups (Drug+ SRP and Drug group). Superior decrease than the control group.Conclusion: Taking vitamin D3 and K2 supplements along with non-surgical periodontal treatment could be a good option for treatment in the future